14x/-3 y /-3

____________

7x/-4 y-3

and the whole equation is in ( ) raised to the -2

14x/-3 y /-3

____________

7x/-4 y-3

and the whole equation is in ( ) raised to the -2

Tutors, please sign in to answer this question.

Kristine -

I'm not sure I can reproduce your equation, so I'm going to answer generally:

When you have a negative exponent, then that means you take the reciprocal of what is raised to the exponent, and the exponent becomes positive. Some examples to clarify:

x^{-2} = 1/(x^{2})

1/(x^{-2}) = x^{2}

(x^{-2})/(y^{-3}) = y^{3}/x^{2 }<=== since both x and y have negative exponents, we take the reciprocal of each.

(x-3)^{-3}(y+3)^{2} = (y+3)^{2}/(x - 3)^{3} <=== since (x-3) has a negative power and is in the numerator, it moved to the denominator

(2x/3 + 5)^{2} [1/(3x/5 - 4)^{-4} ]= (2x/3 + 5)^{2} (3x/5 - 4)^{4
}<=== (3x/5 - 4) has a negative power in the denominator, so it moves to the numerator. No changes are made to the fractions within the parentheses.

Hope that helps you get started.